Serum osteopontin: a biomarker of disease activity and predictor of relapsing course in patients with giant cell arteritis. Potential clinical usefulness in tocilizumab-treated patients. Issue 2 (22nd December 2017) - Prieto-González, Sergio; Terrades-García, Nekane; Corbera-Bellalta, Marc; Planas-Rigol, Ester; Miyabe, Chie; Alba, Marco A; Ponce, Ariel; Tavera-Bahillo, Itziar; Murgia, Giuseppe; Espígol-Frigolé, Georgina; Marco-Hernández, Javier; Hernández-Rodríguez, José; et al.
Abstract : Background: Osteopontin (OPN) is a glycoprotein involved in Th1 and Th17 differentiation, tissue inflammation and remodelling. We explored the role of serum OPN (sOPN) as a biomarker in patients with giant cell arteritis (GCA). Methods: sOPN was measured by immunoassay in 76 treatment-naïve patients with GCA and 25 age-matched and sex-matched controls. In 36 patients, a second measurement was performed after 1 year of glucocorticoid treatment. Baseline clinical and laboratory findings, as well as relapses and glucocorticoid requirements during follow-up, were prospectively recorded. sOPN and C reactive protein (CRP) were measured in 32 additional patients in remission treated with glucocorticoids or tocilizumab (interleukin 6 (IL-6) receptor antagonist). In cultured temporal arteries exposed and unexposed to tocilizumab, OPN mRNA expression and protein production were measured by reverse transcription polymerase chain reaction (RT-PCR) and immunoassay, respectively. Results: sOPN concentration (ng/mL; mean±SD) was significantly elevated in patients with active disease (116.75±65.61) compared with controls (41.10±22.65; p<0.001). A significant decline in sOPN was observed in paired samples as patients entered disease remission (active disease 102.45±57.72, remission 46.47±23.49; p<0.001). sOPN correlated with serum IL-6 (r=0.55; p<0.001). Baseline sOPN concentrations were significantly higher in relapsing versus non-relapsing patients (relapsers 129.08±74.24, non-relapsers 90.63±41.02; p=0.03). OPN mRNA expression and protein production in cultured arteries were not significantly modified by tocilizumab. In tocilizumab-treated patients, CRP became undetectable, whereas sOPN was similar in patients in tocilizumab-maintained (51.91±36.25) or glucocorticoid-maintained remission (50.65±23.59; p=0.49). Conclusions: sOPN is a marker of disease activity and a predictor of relapse in GCA. Since OPN is not exclusively IL-6-dependent, sOPN might be a suitable disease activity biomarker in tocilizumab-treated patients.